تأثير طرائق الحراثة في تحليل النمو لصنف الفول الاسباني ألفا دوسلي - عبد العزيز محمد علي; نقولا ميشيل زكي (Latakia University Journal -Biological Sciences Series, 2013)
نفذ البحث خلال الموسميين الزراعيين 2009-2010 في منطقة القصير غرب مدينة حمص، لدراسة تأثير طرائق الحراثة في تحليل النمو لصنف الفول الاسباني (ألفا دوسلي). استخدم لذلك أربعة طرائق للحراثة هي: 1. حراثة سطحية شاهد (T1). 2. حراثة مطرحية (T2). 3. حراثة قرصية (T3). 4. حراثة شاقة (T4). صممت التجربة بطريقة القطاعات العشوائية الكاملة في خمس مكررات،بينت الدراسة النتائج التالية: تفوقت طرائق الحراثة المطرحية (T2)، والقرصية (T3)، والشاقة (T4) معنويا على الحراثة السطحية (T1) في وزن الأوراق إلى وزن النبات (LWR)، وفي معدل النمو النسبي للورقة (RLGR)، وفي المساحة النسبية للأوراق (LAR)، وفي فترة بقاء الأوراق على كفاءتها في عملية التمثيل الضوئي (LAD)، وفي معدل النمو المحصولي (GGR)، وفي الكفاءة التمثيلية لإنتاج المادة الجافة (NAR). تفوقت الحراثة الشاقة (T4) معنويا على طريقتي الحراثة المطرحية (T2)، والقرصية (T3) في كافة المؤشرات الفيزيولوجية المذكورة أعلاه،بالمقابل لم توجد فروق معنوية بين الحراثة المطرحية (T2)، والحراثة القرصية (T3) في جميع المؤشرات التي تتم دراستها. The research was carried out during 2009-2010 in agricultural seasons, in Alqusser area, western south of Homs city to study growth analysis of Spanish faba bean (var.alfa docle) under the effect of different ploughing methods on leaf weight ratio (LWR) relative leaf growth rate (RLGR), leaf area ratio (LAR), leaf area duration (LAD), crop growth rate (GGR) and net assimilation rate (NAR), using four ploughing methods: surface tillage(T1), disk tillage (T2), place tillage (T3) and disk-turning (T4).the experiment was designed at randomized complete blocks, with five replications. The study showed the following: The ploughing methods of disk Tillage (T2), Place tillage (T4), and disk- Surface Tillage (T1) had a Significant increase in leaf weight Ratio (LWR), Relative leaf growth Rate (RLGR), leaf Area Ratio (LAR, leaf Area Duration (LAD), Crop Growth Rate (GGR) and Net Assimilation Rate (NAR) during the Tow seasons. Disk-turning (T4) had significant increase over disk-tillage (T2), and place tillage (T3) in all physiological indicators mentioned above (LWR, RLGR, LAR, LAD, GGR, and NAR). On another hand, there was no significant increase between ploughing methods disk-tillage and place tillage in all studies indicators.